Balanced Scorecard implementation in small companies: a literature review - Argüello-Solano, Estefanie (2015)
The Balanced Scorecard (BSC) has been used for performance measurement and strategy management for many years. This literature review analyzed studies about the implementation of the BSC in small companies, identifying implementation cases of BSC reported in small enterprises, factors of influence of small enterprises to implement the BSC model, main stages of implementation of the BSC in small enterprises, and future research lines. As a result 23 papers, 12 academic theses and 8 industry reports were identified. Our results shown that small enterprises can take advantage of its specific characteristics to implement the BSC and the implementation process in small companies may differ from the original BSC implementation process. There is little literature on the implementation of the BSC in small businesses, thus it is necessary additional empirical evidence on the effectiveness of CMI implementations in small businesses.